Autonomic seizures and autonomic status epilepticus in early onset benign childhood occipital epilepsy (Panayiotopoulos syndrome) Crises autonômicas e status epilepticus autonômico na epilepsia occipital benigna da infância de início precoce (síndrome de Panayiotopoulos) - Gloria Maria Almeida Souza Tedrus; Lineu Corrêa Fonseca (Arquivos de Neuro-Psiquiatria)
To study clinical and EEG features of children with ictal vomiting and no underlying brain lesions (Panayiotopoulos syndrome). The subjects were 36 children aged 2-13 years. The onset of seizures occurred between 1 and 5 years of age. Fourteen children (38.8%) had a single seizure. Fourteen children (38.8%) had autonomic status epilepticus. Impairment of consciousness was reported in 30 (83.3%) children, eye deviation in 10 (27.7%) other autonomic symptoms and head deviation in 9, generalization in 8, visual symptoms in one child, and, speech arrest or hemifacial motor symptoms in 8 cases. The EEG showed occipital spikes or spike-wave complexes in 27 (75.0%) children, blocked by opening of the eyes in 8 (22.2%) cases. Nine patients (25%) also had rolandic spikes and 3 had extraoccipital spikes. Six (16.6%) patients had normal EEG. No clinical differences were observed between patients having occipital or extraoccipital spikes. In children only with autonomic seizures, the spikes are predominantly occipital but blockage by opening of the eyes is a less frequent feature. In some children there is an overlapping of different focal childhood idiopathic syndromes. Estudar aspectos clínico-eletrencefalográficos de crianças com vômito ictal e sem sinais de lesão cerebral (síndrome de Panayiotopoulos). Foram estudadas 36 crianças na faixa etária de 2-13 anos. O início das crises ocorreu entre 1 e 5 anos de idade. Quatorze crianças tiveram crise única. Status epilepticus foi observado em 14 (38,8%) casos. Distúrbio da consciência foi relatado em 83,3% das crianças, desvio ocular em 27,7%, outros sintomas autonômicos e desvio da cabeça em 26,4%, generalização em 23,5%, bloqueio da fala ou sintomas motores da hemiface em 23,5% das crianças e sintomas visuais em um caso. O EEG mostrou pontas ou complexos de ponta-onda em 27 (75,0%) casos, bloqueados pela abertura dos olhos em 8 (22,2%) pacientes. Nove pacientes tiveram também pontas rolândicas e 3, pontas extraoccipitais outras. O EEG foi normal em 6 crianças. Não houve diferença clínica entre as crianças com pontas occipitais e extraoccipitais. Em crianças com crises autonômicas as pontas foram de predomínio occipital, mas bloqueio pela abertura dos olhos foi pouco freqüente. Em alguns casos houve sobreposição de diferentes síndromes idiopáticas focais da infância.